Structure of polymer and particle aggregates in hydrogel composites. Issue 6 (18th December 2012) - Berts, Ida; Gerelli, Yuri; Hilborn, Jöns; Rennie, Adrian R.
Abstract Knowledge of the structure of a biomaterial is usually vital to control its function. This article provides a structural characterization of a hyaluronan scaffold that has demonstrated good biocompatibility and is used to induce bone regeneration. Hyaluronan hydrogels are appealing materials that can function as a matrix to incorporate both organic and inorganic substances to enhance tissue growth. Because of the intrinsic properties of this swollen matrix, one needs a very sensitive technique that can be applied in situ to determine the organization of the polymers in a gel. Small‐angle neutron scattering is used to determine the characteristics of the inhomogeneous structure of the hydrogel both with and without added particles. The results are interpreted using models of structure with two length scales that are beyond the traditional picture of homogeneous gels. The observed structure and the dimensions can explain the previously reported rheological properties of gels containing different amount of polymers. Hydroxyapatite nanoparticles added to the gel are frozen in the gel matrix. We are able to determine the distribution and shape of these particles as they aggregate around the polymer chains. We have also concluded, in this case, that the particle structure is concentration independent. Information about the nanostructure for an applicable biomaterial guides the formulation, preparation, and use that should lead to further understanding of its exploitation. © 2012 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys, 2013